2020
DOI: 10.1016/j.jvs.2020.04.489
|View full text |Cite
|
Sign up to set email alerts
|

An increased severity of peripheral arterial disease in the COVID-19 era

Abstract: Cardiovascular examination should also include peripheral arterial evaluation for COVID-19 patientsThe global impact of coronavirus disease (COVID-19) on vascular surgical services has been initially addressed by Ng et al. 1 This change in how vascular surgery

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 2 publications
3
40
0
2
Order By: Relevance
“…Our results align with other early studies demonstrating increased amputation rates and peripheral artery disease severity in the setting of the COVID-19 pandemic. 8 , 9 Recent publications outside of vascular surgery suggest we are not alone in our observation of negative pandemic-related effects. A recent study found that weekly rates of hospitalization for acute myocardial infarction decreased by 48% during the pandemic, suggesting that emergent patient needs are likely not being addressed.…”
Section: Discussionmentioning
confidence: 97%
“…Our results align with other early studies demonstrating increased amputation rates and peripheral artery disease severity in the setting of the COVID-19 pandemic. 8 , 9 Recent publications outside of vascular surgery suggest we are not alone in our observation of negative pandemic-related effects. A recent study found that weekly rates of hospitalization for acute myocardial infarction decreased by 48% during the pandemic, suggesting that emergent patient needs are likely not being addressed.…”
Section: Discussionmentioning
confidence: 97%
“…Physical examinations were reduced significantly, which may have led to delays in diagnosis and treatment of patients without COVID-19. In line with this, Sena and Galleli (2020) 5 describe a significantly greater number of amputations performed in their surgery department during the COVID-19 lockdown in Italy. In our clinic, all elective surgeries were postponed; only urgent surgical care was delivered.…”
Section: Introductionmentioning
confidence: 83%
“…However, Sena and Galleli (2020) describe the same findings in their study during the lockdown period in Italy. 5 They report 9 amputations during the lockdown period in 2020 compared with 5 amputations in 2019. 5 We recommend further investigation of the reported effects in a multicenter study.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these observations, we detected a marked decline in the admission rates for acute limb ischemia during the pandemic. Whether this translates into increased disease severity and worse outcomes as others have suggested [26] will need to be investigated.…”
Section: Discussionmentioning
confidence: 99%